2016
DOI: 10.1152/ajpendo.00037.2016
|View full text |Cite
|
Sign up to set email alerts
|

Gut hormone secretion, gastric emptying, and glycemic responses to erythritol and xylitol in lean and obese subjects

Abstract: Wölnerhanssen BK, Cajacob L, Keller N, Doody A, Rehfeld JF, Drewe J, Peterli R, Beglinger C, Meyer-Gerspach AC. Gut hormone secretion, gastric emptying, and glycemic responses to erythritol and xylitol in lean and obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
114
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 40 publications
13
114
0
4
Order By: Relevance
“…The biological mechanisms for the association between artificial sweetener and weight gain are proposed to relate to gut microbiota metabolism (31). Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings. A study in patients with diabetes reported that erythritol and enrichment of another PPP biomarker (ribose) were increased in patients with diabetic retinopathy, and suggested that polyol pathway flux may yield biomarkers of clinical risk in diabetes (34).…”
Section: Discussionsupporting
confidence: 91%
“…The biological mechanisms for the association between artificial sweetener and weight gain are proposed to relate to gut microbiota metabolism (31). Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings. A study in patients with diabetes reported that erythritol and enrichment of another PPP biomarker (ribose) were increased in patients with diabetic retinopathy, and suggested that polyol pathway flux may yield biomarkers of clinical risk in diabetes (34).…”
Section: Discussionsupporting
confidence: 91%
“…Reduced gastric emptying and increased intestinal propulsion can reduce nutrient absorption and food intake in the intestine [10] , our study found that gastric emptying in diabetic rats increased, which is similar to the clinical manifestations of most patients with type 2 diabetes [11] . This study found that gastric emptying in diabetic rats after intramuscular administration of myo-inositol was delayed, and both normal and diabetic rats showed an increase in the intestinal propulsion rate of the eel, which may be due to the similar structure of myo-inositol and glucose.…”
Section: Discusssupporting
confidence: 72%
“…Pre-load beverages with aspartame or saccharin also greatly increased preferences for savoury and high-protein food compared to plain water (Rogers et al., 1988). To our knowledge, only one recent study tested the effects of LCBS (Wölnerhanssen et al., 2016). …”
Section: Discussionmentioning
confidence: 99%